2D X-ray diffraction and molecular modelling of the crystalline structure of polyesters under uniaxial stress. Issue 7 (September 2021) - Abou-Kandil, Ahmed I; Goldbeck, Gerhard
Studying the crystalline structure of uniaxially and biaxially drawn polyesters is of great importance due to their wide range of applications. In this study, we shed some light on the behaviour of PET and PEN under uniaxial stress using experimental and molecular modelling techniques. Comparing experiment with modelling provides insights into polymer crystallisation with extended chains. Experimental x-ray diffraction patterns are reproduced by means of models of chains sliding along the c-axis leading to some loss of three-dimensional order, i.e. moving away from the condition of perfect register of the fully extended chains in triclinic crystals of both PET and PEN. This will help us understand the mechanism of polymer crystallisation under uniaxial stress and the appearance of mesophases in some cases as discussed herein.